Pengaruh Kinerja Keuangan terhadap Financial Distress pada Perusahaan Subsektor Ritel yang Termasuk ISSI - Ahmad Infithar (Lembaga Yasin AlSys, 2025)
Although financial performance has been widely studied, there remains a significant gap in comprehensive studies that focus on effectively addressing situations of financial distress, particularly in manufacturing companies listed on sharia stock indices. This study aims to analyze the effect of financial performance on financial distress in manufacturing sub-sector companies included in the Indeks Saham Syariah Indonesia (ISSI) during the period 2020–2023. The research uses secondary data with a descriptive quantitative approach, with a sample of 8 out of 21 companies selected through purposive sampling. Data were analyzed using descriptive statistics, panel data regression analysis, selection of the appropriate panel regression estimation model, classical assumption tests, hypothesis testing, and the coefficient of determination (R²). The results show that, partially, the Activity Ratio has a positive and significant effect on financial distress, the Solvency Ratio has a negative and significant effect on financial distress, whereas the Liquidity Ratio has a positive but not significant effect. Simultaneously, the Activity Ratio, Liquidity Ratio, and Solvency Ratio have a positive and significant effect on financial distress. These findings indicate that companies need to maximize asset efficiency, reduce the level of debt, and increase equity to avoid financial distress, while also providing practical insights for management in financial decision-making and in managing the risk of financial distress in sharia-based manufacturing companies.